1996
DOI: 10.1063/1.116277
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of ion implanted boron in preamorphized silicon

Abstract: Transient enhanced diffusion of boron in preamorphized and subsequently regrown Si was studied by secondary ion mass spectrometry SIMS and transmission electron microscopy TEM. A comparison of 4 keV, 1 10 14 /cm 2 boron implants into crystalline and Ge preamorphized silicon was undertaken. Upon annealing the B implant into crystalline material exhibited the well-known transient enhanced diffusion TED. In this case the peak of the boron distribution was relatively immobile and only B in the tail showed TED. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…[13][14][15] The results reported in this article could have important implications for the use of fluorine in the realization of future generation devices. The preamorphization implant leaves a damage band, rich in Is, just beyond the original amorphous-crystalline ͑a-c͒ interface.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The results reported in this article could have important implications for the use of fluorine in the realization of future generation devices. The preamorphization implant leaves a damage band, rich in Is, just beyond the original amorphous-crystalline ͑a-c͒ interface.…”
Section: Introductionmentioning
confidence: 99%
“…Another consequence of deep pre-amorphization is the reduced formation of BICs, as previous experiments showed that BICs do not form in preamorphized, and then regrown layers. 13,14 It should also be noted that secondary Ge effects, such as band gap narrowing and strain, are expected to be minimal. Band gap difference at the Ge profile peak concentration of ϳ1.5ϫ 10 21 cm −3 should not exceed 15 meV at room temperature, after Weber and Alonso.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors have observed that in the EOR, at short times at moderate temperatures, there is initially a large number of ͕311͖ defects and a smaller number of dislocation loops. [10][11][12] With the progression of annealing to longer times, the number of ͕311͖ defects decreases and the number of dislocation loops increases. At longer times and higher temperatures, ͕311͖ defects disappear and only dislocation loops remain.…”
Section: ͓S0003-6951͑00͒00807-x͔mentioning
confidence: 99%